A red orange and lemon by‐products extract rich in anthocyanins inhibits the progression of diabetic nephropathy. Issue 12 (29th May 2019) - Damiano, Sara; Lombari, Patrizia; Salvi, Erika; Papale, Massimo; Giordano, Antonio; Amenta, Margherita; Ballistreri, Gabriele; Fabroni, Simona; Rapisarda, Paolo; Capasso, Giovambattista; Forte, Iris Maria; Barone, Daniela; et al.
Abstract: The major cause of end‐stage renal disease is the diabetic nephropathy. Oxidative stress contributes to the development of type II diabetes mellitus (T2DM). In this study we have evaluated the effect of a diet with a new standardized of red orange and lemon extract (RLE) rich in anthocyanins (ANT) in the progression of the kidney disease on Zucker diabetic fatty rats. Oxidative stress and renal function were analyzed. In diabetic rats, the RLE restored the blood glucose levels, body weight, and normalized the reactive oxygen species (ROS) total pathways. The kidney inflammation, in diabetic rats, has not shown significant change, showing that the oxidative stress rather than to inflammatory processes is a triggering factor in the renal complication associated with T2DM. Therefore, the administration of the RLE prevents this complication and this effect could be related to the inhibition of ROS production. Abstract : The present study was designed to evaluate the preventive effects of a new red orange and lemon extract (RLE), on the progression of diabetic nephropathy.